Partido estrutural enquanto linguagem na arquitetura contemporânea - Bittencourt, Daniel Hummel (2007)
With the intent of better understanding and defining how large scale public spaces, in which esthetic connotation is based on form, are formed first as a concept and then physically, shall be presented in this work questions regarding the different classes of structural systems, construction materials, construction techniques, design techniques, as well as the cultural streams which have been a major influence on projects where the most representative architecture reveals itself.